Diabetes Mellitus Tipe 1 - Fauziani, Andra Nabila; Adelia, Anggi; Ardika, Okta Besti; Himayani, Rani; Rahmanisa, Soraya (Medula, 2024)
Diabetes mellitus (DM) is a chronic condition with an increasing incidence worldwide. Not only does it occur in adults, but the incidence rate in children is also quite high. Type-1 DM is an autoimmune disease characterized by absolute insulin deficiency due to pancreatic gland cell damage. Although it can occur at any age, type-1 DM most commonly appears in adolescence with a peak onset around puberty. Diabetes mellitus is often caused by genetic factors and a person's lifestyle. Symptoms of Type 1 DM in children are the same as in adults: polyphagia, polydipsia, polyuria and nocturia, weight loss, and about a third suffer from diabetic ketoacidosis. Complications of diabetes can be divided into microvascular and macrovascular. Microvascular complications include nervous system damage (neuropathy), renal system damage (nephropathy) and eye damage (retinopathy), but can also affect cognitive function, heart and other organs. HbA1c screening is recommended every 3 to 6 months. HbA1c levels reflect glycemic control over the previous 2-3 months. The target HbA1c is generally <7.0%. Other laboratory tests include lipid profile, serum creatinine, eGFR, and urine albumin to creatinine ratio. Management of Type 1 DM includes insulin injection, blood sugar monitoring, nutrition, physical activity, and education. The goal of insulin therapy is to ensure that insulin levels in the body are sufficient for 24 hours to meet metabolic needs due to the glycemic effect of food.